Toward Country-led Development : A Multi-Partner Evaluation of the Comprehensive Development Framework--Findings from Six Country Case Studies - World Bank (Washington, DC, 2013)
Collectively, the six country case studies provide an unusually rich source of material on the local dynamics of the aid business and the realities that countries face when they try to adopt CDF principles in earnest. In order to make this material more accessible (full case studies are over 70 pages), OED has summarized each study to about 15 pages and gathered all six summaries into this volume, which is intended to complement the main synthesis report for the CDF evaluation, Toward Country-Led Development: A Multi-Partner Evaluation of the Comprehensive Development Framework. This volume can also be used alone, to enrich the discussion of development assistance in a particular case study country or as a basis for comparing country experiences. Since the main purpose of the CDF evaluation was to look at what had happened since the CDF was launched, priority was given to interested countries where pilot implementation of the CDF was the most advanced (on the grounds that these countries would offer the greatest potential for learning). Consideration was also given to Regional balance. One non-CDF pilot country (Burkina Faso) was chosen as a control.